1978
DOI: 10.1017/s0021859600055386
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the nutrition of the dairy heifer

Abstract: SummaryEight experiments, comprising four randomized-block feeding trials each with 20–45 animals and four changeover-design nitrogen (N) balance trials each with 6–10 animals, were used to study the effect of the addition of formaldehyde to fishmeal and to casein, of severe heating of fishmeal, and of tannin treatment of a mixture of vegetable protein-rich foods on the utilization of N for growth. Added in moderate amounts to rations demonstrated within the experiments to be deficient in N, quantities, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
3

Year Published

1981
1981
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
6
12
3
Order By: Relevance
“…Live-weight change increased with greater intakes of DDMI, the size of the response declining in mid and late lactation. This disagrees with the evidence of Broster et al (1969Broster et al ( , 1975 that the response in live-weight change increased as the lactation continued whereas that in milk yield declined. The explanation of this apparent anomaly must await further evidence on body composition for elucidation.…”
Section: Response To Ddmicontrasting
confidence: 99%
See 2 more Smart Citations
“…Live-weight change increased with greater intakes of DDMI, the size of the response declining in mid and late lactation. This disagrees with the evidence of Broster et al (1969Broster et al ( , 1975 that the response in live-weight change increased as the lactation continued whereas that in milk yield declined. The explanation of this apparent anomaly must await further evidence on body composition for elucidation.…”
Section: Response To Ddmicontrasting
confidence: 99%
“…They made greater gains in the first lactation compared with H and M, such that mean post-calving live weights per treatment after the second parturition were similar. There was no correlation between initial live weight after first calving and gain during that lactation for individual animals, in agreement with the observation by Broster et al (1969Broster et al ( , 1975, see Broster& Broster (1984). From week 36 of the first lactation to second parturition the M animals made greater gsins than the AL group, with H and M intermediate (Table 23).…”
Section: Ags 104supporting
confidence: 90%
See 1 more Smart Citation
“…The lactation curve parameters were unaffected. Broster, Broster, Smith and Siviter (1975) have further strengthened this view in a series of feeding trials in which variations in the fundamental curve corresponded closely with changes in the experimental diet.…”
Section: Resultsmentioning
confidence: 74%
“…Restricting energy intake of primiparous cows, whether intentional or not, might be detrimental to milk yield because these cows have requirements for growth in addition to pregnancy and lactation (NRC, 2001). Some studies that have focused on the effect of plane of nutrition on subsequent lactational performance in primiparous cows have indicated that a higher plane of nutrition prepartum may confer advantages over restriction of nutrients prepartum (Broster and Tuck, 1967;Park et al, 1987). In contrast, Lacasse et al (1993) found no advantage of overfeeding primiparous cows before their first lactation on milk yield or milk components.…”
Section: Introductionmentioning
confidence: 99%